DormTalk: edge computing for the dormitory applications on campus. Issue 3 (1st May 2019) - Lin, Yi‐Bing; Shieh, Min‐Zheng; Lin, Yun‐Wei
Abstract : Internet of things (IoT) connects a large number of edge IoT devices to produce huge volumes of data. To effectively manipulate the real‐time IoT data, it is essential to integrate edge computing with the cloud computing. This study investigates how real‐time IoT applications benefit from edge computing. Specifically, the authors show how edge computing and cloud computing can be nicely integrated to build a smart campus environment in National Chiao Tung University (NCTU). Based on an IoT device management platform called IoTtalk, the authors develop an edge IoT computing system called DromTalk for dormitory applications in NCTU. Conventional approaches are difficult to interact with IoT servers of different platforms. The authors' approach proposes a novel method that uses a cyber IoT device to nicely bridge the IoTtalk server in the cloud and the DormTalk servers at various dormitory buildings (the edges) without modifying these servers. The authors investigate the response time performance of the edge DormTalk server, which shows that smartphones can effectively control the dormitory appliances with good user experience.